NILAI BUDAYA DALAM CERITA RAKYAT JAMBU LIPO - Putri Mayang Sari (Jurnal Elektronik WACANA ETNIK, 2012)
This article describes analysis result on cultural contents of Jambu Lipo folktales. Jambu Lipo is one of  kingdoms  in  Minangkabau teritory. These  folktales  analyzed with Kluckhohn and Srtodtbeck theory. The result shows relationship between human and nature, human and their jobs, and between human  and human.